Dynamics of an authoritarian system Hungary, 2010-2021 - Csanádi, Mária; Gerő, Márton 1980-; Hajdu, Miklós; Kovács, Imre; Laki, Mihály 1946-; Tóth, István János 1960- (Central European University Press, 2022)
This conceptually synthetic and empirically rich book demonstrates the vulnerability of democratic settings to authoritarianism and populism. Six scholars from various professional fields explore here the metamorphosis of a political party into a centralized authoritarian system. Viktor Orbán and his Fidesz party needed less than ten years to accomplish this transformation in Hungary. In 2010, after winning a majority that could make changes in the constitution - two-thirds of the parliamentary seats, they evolved and stabilized the system, which produced again the two-thirds majority in 2014 and 2018. The authors reveal how a democratic setting can be used as a device for political capture. They show how a political entity managed to penetrate almost all sub-fields of the economy to arrive at institutionalized corruption, and how the centralized power structure reproduces itself. With the help of a powerful empirical apparatus-among others analyses of more than 220,000 public tenders, redistributions of state subsidies, and the interconnectedness of those privileged with the political elite - the authors detail the functioning of a crony system and the network aspects of political connections in the rapid enrichment of politically-linked businesses. Their studies demonstrate the role of political capture in this redistribution and how this capture leads to a new social stratification